2020
DOI: 10.1515/cclm-2019-0869
|View full text |Cite
|
Sign up to set email alerts
|

A liquid chromatography-tandem mass spectrometry (LC-MS/MS)-based assay to profile 20 plasma steroids in endocrine disorders

Abstract: BackgroundLiquid chromatography-tandem mass spectrometry (LC-MS/MS)-based assays are employed in more and more clinical laboratories to quantify steroids. The steroid quantification by LC-MS/MS shows great value in screening or diagnosing endocrine disorders; however, the number of functional steroids included in the LC-MS/MS methods is still limited.MethodsHere, we describe the performance and validation of a 20-steroid plasma panel by LC-MS/MS. The panel included progestogens (including mineralocorticoids an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 34 publications
0
45
0
Order By: Relevance
“…2,37,38 In Guo et al's recent study, with a smaller patient cohort, also confirmed that T, A4, and DHT together might contribute to the more accurate diagnosis of PCOS. 39 Similarly, in present study, the However, according to their logistic regression study using forward stepping models, it was found that their large steroid panel was no According to the current PCOS diagnosis guideline, 38 it is required and necessary to exclude the possibility of NCAH mimicking the symptoms of PCOS. In a recent review article comparing PCOS and NCAH, 41 on average, 87% of NCAH patients and 25% of PCOS patients showed elevated serum 17-OHP levels, which was the only recommended screening assay to differentiate the two distinct diseases requiring different therapeutic treatments.…”
Section: F I G U R Ementioning
confidence: 47%
See 1 more Smart Citation
“…2,37,38 In Guo et al's recent study, with a smaller patient cohort, also confirmed that T, A4, and DHT together might contribute to the more accurate diagnosis of PCOS. 39 Similarly, in present study, the However, according to their logistic regression study using forward stepping models, it was found that their large steroid panel was no According to the current PCOS diagnosis guideline, 38 it is required and necessary to exclude the possibility of NCAH mimicking the symptoms of PCOS. In a recent review article comparing PCOS and NCAH, 41 on average, 87% of NCAH patients and 25% of PCOS patients showed elevated serum 17-OHP levels, which was the only recommended screening assay to differentiate the two distinct diseases requiring different therapeutic treatments.…”
Section: F I G U R Ementioning
confidence: 47%
“…In Guo et al's recent study, with a smaller patient cohort, also confirmed that T, A4, and DHT together might contribute to the more accurate diagnosis of PCOS 39 . Similarly, in present study, the combinational use of the four‐androgens provided optimum PCOS discrimination with the ROC analyses with the best sensitivity and specificity, suggesting their potential diagnostic value as a testing panel, although the cutoff values for each analyte needs to be further validated in independent cohorts.…”
Section: Discussionmentioning
confidence: 81%
“…An internal standard for the peptide group was not used in the current study; search parameters were strictly controlled to ensure the accuracy of data. Filter parameter setting were as follows: 0≤ retention time ≤50; feature significance, ≥0; feature fold change, ≥1; 1≤ charge ≤10; with peptide ID: True; protein significance, ≥20; protein fold change, ≥2; significance method: PEAKSQ; confident unique supports, ≥1; normalization use Total Ion Chromatography; search parameter settings: Quantification type: Label free quantification; mass error tolerance, 20.0 ppm; retention time shift tolerance, 4.0 min; dependent on PID ( 25 ): 20; False Discovery Rate threshold, 1%.…”
Section: Methodsmentioning
confidence: 99%
“…Testosterone and cortisol, being abundant, were relatively swiftly switched to MS analysis in clinical biochemistry and research settings, but estrogens, particularly in lower ranges (Figure 1), presented challenges, for example assessing effectiveness of aromatase inhibitors in women recovering from breast cancer, where residual hormone may promote tumour regrowth [19]. Although the resolving power of LC is not as good as GC, ongoing improvements in LC technology are enabling multi-steroid profiling, albeit some steroids having poorer sensitivity and isomer separation remains challenging [20,21]. A further benefit of LC over GC is the ability to include conjugates in the analyte profile [22].…”
Section: The Art Of Separationmentioning
confidence: 99%